1990
DOI: 10.1017/s0956536100000080
|View full text |Cite
|
Sign up to set email alerts
|

New Data on Sources of Obsidian Artifacts from Tikal, Guatemala

Abstract: In 1984, 29 obsidian artifacts and an unworked nodule from Tikal were attributed to source by visual means and then analyzed by X-ray fluorescence (XRF). We conclude that the considerable within-source optical variability of gray Mesoamerican obsidians makes visual sourcing unreliable at present, although a corpus of descriptions of the optical characteristics of obsidian may eventually provide a way to exclude possible sources. The XRF analysis identified two additional central Mexican sources, bringing to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 7 publications
2
36
0
Order By: Relevance
“…Pachuca obsidian blades also have been recovered in relatively high numbers along the west and north coastal port sites in the Yucatan (Andrews et al , 1989, but along the eastern coast, Pachuca obsidian is found only in small numbers relative to other types (McKillop 1989(McKillop , 1995a(McKillop , 2004. There is limited evidence for the production of blades from Pachuca cores at these sites, and instead finished blades or bifaces may have been transported (McKillop 1989;Moholy-Nagy and Nelson 1990), which runs counter to the pattern predicted for blade production from other sources. A review by Spence (1996) of Pachuca obsidian in Maya contexts has built a good case that much of the greengold obsidian changed hands as gifts and not as a commodity.…”
Section: Human Activity Indicatorsmentioning
confidence: 89%
“…Pachuca obsidian blades also have been recovered in relatively high numbers along the west and north coastal port sites in the Yucatan (Andrews et al , 1989, but along the eastern coast, Pachuca obsidian is found only in small numbers relative to other types (McKillop 1989(McKillop , 1995a(McKillop , 2004. There is limited evidence for the production of blades from Pachuca cores at these sites, and instead finished blades or bifaces may have been transported (McKillop 1989;Moholy-Nagy and Nelson 1990), which runs counter to the pattern predicted for blade production from other sources. A review by Spence (1996) of Pachuca obsidian in Maya contexts has built a good case that much of the greengold obsidian changed hands as gifts and not as a commodity.…”
Section: Human Activity Indicatorsmentioning
confidence: 89%
“…The surface of the nodule was pitted, and the glass was remarkably free of crystallites. Because of these characteristics it was suggested that this specimen might We report here a magnetic study on three of the specimens described in the above studies and designated as 12T-451/79, 20M-97B/41 (same as Moholy-Nagy and Nelson [1990] specimen 1589), and 24F-26/11 (hereinafter referred to as 12T, 20M, and 24F) in an attempt to confirm them as true tektites. Senfile and Thorpe [1959] have shown that magnetic properties can be used to distinguish tektites from obsidian glass.…”
Section: Introductionmentioning
confidence: 92%
“…Visual inspections of raw material lithology can be very useful for determining archaeologically relevant lithological categories (Stout et al, 2005). However, several studies have suggested that hand sample identifications can misclassify sources within major raw material groups (Calogero, 1992;Lanier and Dodd, 1985;Moholy-Nagy and Nelson, 1990;Perry, 1992). Even across major raw material groups misidentifications are common in assemblages of fine grained rocks (Hermes et al, 2001).…”
Section: Raw Materials Sourcingmentioning
confidence: 99%